Perayaan Hari Suci Nyepi sebagai Implementasi Ajaran Yoga - Acyutananda Wayan Gaduh; Mery Ambarnuari (UHN IGB Sugriwa Denpasar, 2020)
Nyepi is a Hindu’s holy day which is celebrated by the Balinese to commemorate the new year Çaka. Nyepi is very uniquecelebration because it is celebrated by eliminating all routines. Nyepi as a religious tradition and ritual can make a real contribution to the preservation of nature. The series of Nyepi ceremonies starts from melasti, nyejer, tawur kesanga, Nyepi day and ends with ngembak geni. The essence of the celebration of the Nyepi Holy Day is Catur Brata Penyepian consisting of: amati geni (not light a fire), amati karya (not working), amati lelungan (not traveling), and amati lelanguan (not eating and enjoying entertainment). At a higher level, Catur Brata Penyepian leads Hindus to hone their quality of self by controlling the inner flames of lust, eliminating physical work to increase spiritual work, increase the inner race, and not fixating on the pleasures of the world. With this understanding, a series of Nyepi ceremonies can be used as a means of discovering true truth within oneself, such as the teachings of yoga. The Astangga Yoga concept presents eight stages of yoga namely yama, nyama, āsana, prānāyāma, pratyāhāra, dhārana, dhyāna and samādhi. Astangga Yoga has been applied in the implementation of the Nyepi Holy Day series by clearing the senses to achieve true truth. The teachings of yoga dissolve in Nyepi Holy Day ceremonial activities which are carried out earnestly and wholeheartedly.